Tourette syndrome and brain stimulation therapy: a systematic review and meta-analysis of current evidence - Aloufi, Alwaleed K.; Zahhar, Jalal A.; Bader, Mahmoud W.; Almutairi, Maher B.; Alaaldeen, Abdulqader; Hetta, Omar E.; Gammash, Abdulaziz M.; Almuntashiri, Saleh; Binrabaa, Ibrahim S.; Alsaleh, Ahmad; AlSalem, Moayyad (Frontiers in Psychiatry, 2025)
BackgroundTourette syndrome (TS) is a neurological disorder characterized by tics, often associated with obsessive-compulsive disorder (OCD). Severe cases may require interventions such as deep brain stimulation (DBS) or repetitive transcranial magnetic stimulation (rTMS).MethodsA thorough search was performed across PubMed/Medline, Embase, (CENTRAL), and Google Scholar. Studies comparing DBS and rTMS efficacy for TS were included if they reported YGTSS before and after treatment. Two independent reviewers screened the search results, extracted data, and assessed study quality using standardized tools.Results22 studies met the inclusion criteria, with a total of 222 participants. Analysis of RCTs investigating post-intervention rTMS vs baseline showed a statistically insignificant decrease in YGTSS (MD = -5.01, 95% CI: [-10.8, 0.79], P= 0.090) but a statistically significant decrease in YBOCS (MD = -6.6; 95% CI: [-11.64, -1.55], P= 0.010). However, post-intervention rTMS in RCT and non-randomized trials vs baseline showed a significant decrease in YGTSS (MD = -11.6; 95% CI: [-18.25, -4.94], P < 0.001) and YBOCS (MD = -7.5; 95% CI: [-11.85, -3.15], P < 0.001). Post-intervention DBS in RCT and non-RCTs vs baseline showed a significant decrease in YGTSS (MD = -18.29; 95% CI: [-24.93, -11.64], P < 0.001) and YBOCS (MD = -4.76; 95% CI: [-7.30, -2.21], P < 0.001). Analysis of RCTs investigating Post-intervention DBS vs baseline showed a significant decrease in YGTSS (MD = -14.71; 95% CI: [-19.78, -9.63], P <0.001) and YBOCS (MD = -5.04; 95% CI: [-8.28, -1.80], P = 0.002).ConclusionOur analysis revealed both DBS and rTMS improved TS and OCD symptoms, however the effect of rTMS on TS in RCTs was insignificant, suggesting DBS stimulation is more effective. Despite this, clinicians may still opt for rTMS before DBS due to its less invasive nature, the limited number of high-quality RCTs, and the lack of studies directly comparing rTMS and DBS.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023386856, identifier CRD42023386856.